RAW WATER QUALITY ANALYSIS TO DISCOVER THE CAUSE OF PIPELINE SCALLING PROBLEM IN PT. X (ICE PRODUCTION COMPANY) - Kadek Diana Harmayani; Gede Adi Wiguna Sudiartha; I Wayan Budiarsa Suyasa (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
PT. X is one of the ice companies in which its largest company is located in Bali, more precisely in the Pidada area, North Denpasar. Based on field observations the area is an area that has a calcareous soil structure. The water source of PT. X was extracted from the groundwater. From the field observation, it was found that the pipeline network, that connected the inlet water to water treatment system and ice production units, was severely covered by faint white scale. In order to discover the origin of this scale, water quality testing need to be carried out.  From the results, it was found that the total hardness in the inlet water, taken from the groundwater tap, was 162.85 mg/l with calcium concentration of 2.15 mg/l and iron 3.83 mg/l. Water quality testing was also carried out in the water treatment unit consisting of resin softener where the total hardness surprisingly increased into 279.81 mg/l, calcium concentration was 2.96 mg/l, iron concentration was 0.55 mg/l. Even after being treated in softener resin, the total hardness increased sharply to 483 mg/l, which categorized as extreme hardness. The increase in total hardness indicates that there was a failure in the operation of the water treatment system, even it also contributed to the higher hardness and calcium concentration. This over-year’s treatment failure has been causing accumulation of hardness and calcium concentration in the compartment of both water treatment system and ice production unit that inflicts a higher hardness level in the effluent.